Andy warhol 365 takes - the staff of the andy warhol musem; the staff of the andy warhol musem; Warhol, Andy, 1928-1987 .; Andy Warhol Museum. . (London : the andy warhol museum, 2004)
andy warhol remains one of the most intriging figures of our time.
Formerly CIP. Uk Includes bibliographical references and index. .
All age.
Keywords: Artists -- United States -- Catalogs. .